Pendidikan Kesehatan tentang Pola Hidup Sehat pada Lansia di Posyandu Lansia SUMUNAR, Sumber, Surakarta - Widia Susanti; Risya Cilmiaty A.R; Betty Saptiwi; Adi Prayitno; Alfiyah Pujiyati; Meirina Mulia Wardani; Satria Wardana; Afrizal Tri Heryadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Sumunar Elderly Posyandu is in Sumber, Surakarta. Elderly (elderly) is someone who has entered the final stages of life. The elderly will experience biological decline which can be seen as symptoms of physical decline as well as physiological changes and changes in the digestive tract. This change will have an impact on all aspects of life, including health. Therefore, knowledge and behavior about healthy lifestyles is very important for elderly people with all the limitations or health problems they have. The aim of this service is to carry out the Community Service component of the Tri Dharma of Higher Education. The benefit of this service is increasing knowledge about healthy lifestyles in the elderly. Implementing a healthy lifestyle according to the type of disease in elderly people who suffer from disease disorders will really help control their disease, so that in the end they can improve their quality of life. The service methods used are lectures, demonstrations and health checks as well as dental and oral examinations. The target audience was 60 elderly people at the Sumunar Elderly Posyandu. The results of the service showed that the activity ran smoothly and participants were enthusiastic about participating in the activity. Participants are expected to be able to implement a healthy lifestyle in their daily lives, by consuming healthy food, exercising regularly and getting enough rest.